A symphony for a common man [videorecording (DVD)] - Joffily, José, 1945-; Berg, Jordana, 1963-; Bustani, Jose (EPF Media, 2024)
The US justification of the invasion of Iraq in 2003 based on Iraq's supposed possession of weapons of mass destruction has long been debunked. The US government wanted to bring about regime change and secure oil interests. Come what may, there was to be war. The US government crushed a potentially successful attempt to prevent the war. Negotiations led by Jose Bustani, director general of the Organization for the Prohibition of Chemical Weapons (OPCW), on Iraq₂s membership in the multilateral organization were scuttled. Because Bustani refused to bow to US demands to stop the negotiations, the US government used fake news about mismanagement to pressure the participating countries in the OPCW to remove him from office. The smear campaign was successful. Nearly twenty years later, Bustani and others involved look back at the American abuse of power as a warning.